Removal of ammonium, iron and manganese from potable water in biofiltration units: a review. Issue 5 (8th March 2013) - Tekerlekopoulou, Athanasia G.; Pavlou, Stavros; Vayenas, Dimitrios V.
Abstract Ammonium, and trace metals such as iron and manganese are common inorganic pollutants present in waters. Several surface and groundwaters contain natural or increased concentrations of these pollutants that are observed either isolated or in pairs, or all three together. Although several processes have been established for the biological removal of one of the above‐mentioned pollutants, only recently have important studies been performed on the efficient and cost‐effective simultaneous biological removal of two or more substances. This paper reviews the variety of full‐ and pilot‐scale biological filters that have been used for combined or simultaneous biological removal, as well as factors and conditions that were found to affect the process. The main results regarding research progress on combined or simultaneous biological removal are evaluated. Finally, the kinetic models and simulation approaches used are discussed. © 2013 Society of Chemical Industry